The postulated model of the prosecutor's participation in the delibation proceedings in civil cases. De lege lata and de lege ferenda remarks - Tomasz Demendecki (Probacja, 2022)
The subject of this study is a critical analysis of the current solutions in the field of civil procedural law, concerning the mechanism of ensuring the effectiveness and enforceability of foreign judgments on the territory of the Republic of Poland. As part of the 2008 amendment to the Code of Civil Procedure, the legislator removed from art. 1148, providing for the obligatory participation of the prosecutor in the delibation proceedings. Contrary to the previously and currently applicable regulations of the civil procedural law, it is proposed to leave the exclusion of the obligatory participation of the prosecutor in the delibation proceedings. At the same time, the possible introduction of the adjudicating court's obligation to inform the indicated public interest ombudsman about the initiation of delibation proceedings is under consideration, leaving the prosecutor an independent decision on whether to join the initiated proceedings (Article 59 in connection with Article 13 § 2 of the Code of Civil Procedure). Such a solution, providing for the obligation of the court to deliver to the prosecutor a copy of each motion initiating delibation proceedings, would be a compromise, because on the one hand it should not result in an excessive increase in the obligations of the prosecutor's office, but on the other hand, in doubtful situations it would allow for the real participation of the prosecutor in the proceedings.